PERENCANAAN TEBAL PERKERASAN KAKU (RIGID PAVEMENT) PADA RUAS JALAN PANDA MANUNGGAL JAYA KECAMATAN SEBULU KABUPATEN KUTAI KARTANEGARA - ANSYAH, ARDI (KURVA S JURNAL MAHASISWA, 2014)
If rigid pavement has reached the end of the maid, so that no longer able to withstand traffic loads that are in it, then there are two options to improve the ability of rigid pavement, namely the reconstruction or replacement of the pavement with concrete pavement that is new, or with plus coating (overlay) on an existing concrete pavement. With the overlay is expected to increase the service life of the old pavement and also can increase the capacity of the structure, reduce the use of equipment for maintenance or maintenance, as well as savecosts. In this final project will be discussed pekerasan rigid structure calculations using the method of SNI, for data traffic and the old pavement thickness are taken together. From the calculation using the method SNI Pd T-14-2003 was obtained parameters are used in every implementation in the field.Keyword : Calculating age of 10 years plan, ARAB and methods SNI Pd -14-2003.1) Karya Siswa Jurusan Teknik Sipil, Fakultasi Teknik, Universitas 17 Agustus 1945 Samarinda.2) Dosen Jurusan Teknik Sipil, Fakultasi Teknik, Universitas 17 Agustus 1945 Samarinda.3) Dosen Jurusan Teknik Sipil, Fakultasi Teknik, Universitas 17 Agustus 1945 Samarinda.